Seizures in children with epilepsy and attention‐deficit/hyperactivity disorder. Issue 10 (30th October 2019) - Goker, Zeynep; Yilmaz, Arzu; Eraslan, Ayse Nihal; Sivri, Rukiye Colak; Aydin, Rezzan
Abstract: Background: Epilepsy is an important disorder that is sometimes accompanied by inattention problems. This study explored the features of seizures in children with epilepsy, with or without attention‐deficit/hyperactivity disorder (ADHD). Methods: Between January 2017 and January 2018, data records of children with epilepsy aged 5–18 years admitted to hospital were retrospectively collected. SPSS 17.0 was used for analyses and P < 0.05 was accepted as significant. Results: Of 301 patients with epilepsy, 32 of them had ADHD. Median age at diagnosis of epilepsy in the epilepsy + ADHD group was lower than in the epilepsy alone group (6 vs 8 years; z = −2.989, P = 0.003). The two groups were similar in terms of duration of epilepsy, seizure types and features of complicated versus non‐complicated epilepsy, number of anti‐epileptic drugs (AED) used (for all, P > 0.05). The epilepsy + ADHD group had a significantly higher prevalence of intellectual disability (31.3% vs 12.6%; χ 2 (1) = 7.9, P = 0.014) and specific learning disorder (12.5% vs 1.9%; χ 2 (1) = 11.1, P = 0.009) than the epilepsy alone group (χ 2 (1) = 11.1, P = 0.009). ADHD medication use was identified in 68.8% of children in the epilepsy + ADHD group. Conclusion: Attention‐deficit–hyperactivity disorder was identified in 11.8% of 5–18‐year‐old children (32/301) with epilepsy in a 1 year period. ADHD is more frequent in children with epilepsy in childhood (5–11 years of age). Epilepsy diagnosis is more frequent in younger children with ADHD. Children with epilepsy and ADHD, also have a significantly higher prevalence of intellectual disability and specific learning disorder. Younger children diagnosed with epilepsy should be carefully monitored for ADHD.